The effect of peer support on foot care in patients with type 2 diabetes - Zahra Ghasemi; Hojatollah Yousefi; Mohsen Torabikhah (Wolters Kluwer Medknow Publications, 2021)
Background: Diabetes mellitus is one of the prevalent diseases in the world with several complications including diabetic foot ulcers. The aim of this study was to investigate the effect of peer support on foot care in patients with type 2 diabetes. Materials and Methods: This clinical trial study was performed at selected centers of Isfahan University of Medical Sciences in 2017. Fifty patients with type 2 diabetes were randomly assigned into intervention and control groups. Five 30-min. supportive training sessions were held for the intervention group by the peers and during 35 days. Foot Care Confidence/Foot-Care Behavior Scale For Diabetes (FCCS-FCB) was completed by both groups before, immediately after and 1 month after the intervention. Collected data were analyzed using Chi-square, Mann-Whitney, repeated measures ANOVA and t-test. Results: Mean (SD) age of subjects was 56.46 (7.36) years old Mean (SD) score of self-efficacy (F2, 26 = 54.71, p < 0.001), preventive behaviors (F2, 26 = 28.46, p < 0.001), and potentially damaging (F2, 26 = 27.89, p < 0.001) had significant differences between the two groups immediately and 1 month after the peer support. Conclusions: Peer support can enhance foot care behaviors in diabetic patients. Therefore, using people who are successful in the education and support of patients has a significant role, and nurses can use them as a support in the field of care and follow-up. However, health agencies are responsible for providing the patients with the best guidelines, and these results can be useful as an evidence for them.